?EFFECTS OF ENTOMOPATHOGENS ON ALBINO MICE - Quadri, Shakira; Anwar, Naheed; Mirza, Maryam; Qureshi, Zamir A; Rizki, Yazdana Mirza (Biological Sciences - PJSIR, 2000)
The safety of three species of entomogenous fungi Tolypocladium cylindrosporum (Gams.), Verticilium lacanii (Zimm.) Viegas and Paecilomyces fumosa-roseus (Wize.) Brown &Smith was tested on laboratory mice. Acute oral dosages of4.9 x 108 spores/mouse for T. cylindrosporum, 5.54 x 108 spores/mouse for V. lacanii and 4.5 x 108 spores/mouse for P.fumosa- rose us were administered for two weeks experimental period. No recoveries of the target organisms were recorded from any of the tested animals and there were no significant differences in terms of body weight, food and water consumption and blood counts. No histopathological changes were observed in liver and kidney on microscopic examination.